Magnetic field profile of a mesoscopic SQUID-shaped superconducting film - Rogeri, F. [UNESP]; Zadorosny, R. [UNESP]; Lisboa Filho, Paulo Noronha [UNESP]; Sardella, Edson [UNESP]; Ortiz, W. A. (IOP Publishing, 2013)
Using a genuinely tridimensional approach to the time-dependent Ginzburg-Landau theory, we have studied the local magnetic field profile of a mesoscopic superconductor in the so-called SQUID geometry, i.e., a square with a hole at the center connected to the outside vacuum through a very thin slit. Our investigation was carried out in both the Meissner and the mixed state. We have also studied the influence of the temperature on the space distribution of the local magnetic field. © 2013 IOP Publishing Ltd.
Keywords: Local magnetic field; Magnetic field profile; Mesoscopic superconductors; Mesoscopics; Mixed state; Space distribution; Time-dependent Ginzburg-Landau theories; Magnetic fields; Molluscs; Shellfish; Superconducting materials